2020
DOI: 10.1111/cyt.12827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine cytology diagnostic reports before and after the implementation of the Paris System classification system in China

Abstract: Objective In 2013, The Paris System for Reporting Urinary Cytology (TPS) was developed as a uniform practical urine cytology system that could be applied worldwide. Here, we investigated the effectiveness of TPS diagnostic approach compared with that of the traditional urine cytological diagnosis method used in China. Methods Based on the diagnostic criteria of TPS, 412 urine samples from 143 patients with histological follow‐up data were retrospectively analysed, and the diagnoses were compared with the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Based on above methods, it is not a surprise that different, even opposite results were obtained in different institutions. For example, the frequency of AUC category was reported to decrease significantly in some institution however unaffected in others as shown in Table 4 3,5,6,17‐20,27,28,30‐39 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on above methods, it is not a surprise that different, even opposite results were obtained in different institutions. For example, the frequency of AUC category was reported to decrease significantly in some institution however unaffected in others as shown in Table 4 3,5,6,17‐20,27,28,30‐39 …”
Section: Discussionmentioning
confidence: 96%
“…For example, the frequency of AUC category was reported to decrease significantly in some institution however unaffected in others as shown in Table 4. 3,5,6,[17][18][19][20]27,28,[30][31][32][33][34][35][36][37][38][39] 5 | CONCLUSION TPS represents a significant improvement in classification of urinary specimens. By using TPS, we are able to provide a uniform classification system focused on the detection of HGUC.…”
Section: Atypical Urothelial Cells Categorymentioning
confidence: 99%
“…However, three other studies reported cases classified as LGUN based on TPS criteria that showed HGUC on follow-up histology. In Ma et al, 6/143 (4.2%) cases were classified as LGUN, and follow-up histology showed LGUN in 4 cases and HGUC in 2 cases, resulting in a sensitivity of 12% and a specificity of 98% [41]. Roy et al classified 13/97 (13%) cases as LGUN, and of those, 3 were HGUC on follow-up biopsy [42].…”
Section: Tissue Fragments Arising From Low-grade Urothelial Neoplasms...mentioning
confidence: 99%
“…The Paris System for Reporting Urinary Cytology (TPS) was issued in 2016 with the aim of properly diagnosing high‐grade urothelial carcinoma (HGUC) and reducing the use of equivocal terms, such as “atypical” and “suspicious.” 1 TPS has addressed the wide variability among observers and facilities, and improved the diagnostic accuracy over that of conventional urinary cytology 2,3 . However, false‐positives of reactive urothelial cells have been reported in studies using TPS 4 .…”
Section: Introductionmentioning
confidence: 99%